PERANCANGAN SEPATU KULIT BERTEMA TOPENG MALANGAN - Yodi Aldy Dharmawan; Gunawan Gunawan; Kumara Sadana Putra (Perpustakaan Universitas Surabaya, 2018)
Malangan mask is one-of Indonesia’s traditional culture which comes from Malang city, precisely coming from the kingdom of Kanjuruhan. Formerly, Malangan mask is used for traditional ceremonies, but by the growing of the era Malangan mask is used for entertain people using folklore. The characters that are famous in that folklore are Panji Asmorobangun and Dewi Sekartaji. By the growing of the era, foreign cultures are coming to Indonesia. It can be seen by young generation that love foreign cultures and modern cultures so that traditional culture from Indonesia faded. To resolve that problem, we begin this study with the purpose of uniting the Indonesia’s traditional culture with modern cultures. A lifestyle products are one of modern cultures. Lifestyle products grow with the era. One of lifestyle product which is popular to use are shoes. From the study, we try to put the Traditional cultures, which is Malangan mask, into a modern product which is shoes. The shoes are casual shoes using genuine leather for the material. This leather shoes design used Vigilant trend, a sub-theme of trend in 2018. Brand names for this lifestyle products is Piedre, which is an acronym of Piece De Resistance that have meaning masterpiece.